The perception of state security by the expert community - Ivan PEZLAR (Košická bezpečnostná revue, 2025)
The state should fulfill key roles such as eliminating negative internal and external influences, protecting economic interests, ensuring the defense of the country, and securing the safety of its citizens. It is also its duty to protect the lives and health of people, maintain public order, provide social security, and ensure the availability of public services.